A review of nickel-molybdenum based hydrogen evolution electrocatalysts from theory to experiment - Park, Sun Hwa; To, Dung T.; Myung, Nosang V. (Applied catalysis. A, General, 2023)
Hydrogen evolution reaction (HER) from alkaline electrolytes is one of most promising methods for producing hydrogen. The remaining obstacles include the development of high performance and earth-abundant electrocatalysts which can be cost-effectively fabricated in large-scale. Ni-Mo based materials are one of potential candidates which might meet the most needs. In this review, we summarize the latest progress in Ni-Mo based HER catalysts in alkaline electrolytes from theoretical calculation to experimental results. This work also summarizes several different strategies to enhance the HER rate. Finally, the future perspective of the next generation electrocatalysts is discussed. [Display omitted] •Latest development of Ni-Mo based electrocatalysts for hydrogen production.•Theoretical calculations and experimental evaluations of various Ni-Mo alloys.•Effective strategies to improve the hydrogen evolution reaction performance.